Fungi decontamination by gaseous ozone of fresh, dried and salted mackerel (Acanthocybium solandri) (Research, Society and Development, 2020)
The aim of this study was to investigate the antifungal effect of ozone gas (O3) (green decontamination agent) on mackerel fish (Acanthocybium solandri) in different types of preservation (fresh, dry and salted). Samples humidity [mc / aw] parameters prior gas treatment, were of 80.7%/0.98, 55.55%/0.74 and 49.5%/0.70, respectively. Fish were contaminated with fungi genera that are able to grow on high (Fusarium) and low (Aspergillus / Penicilliun) moisture content substrates, then gas treated at 50 μmol O3 /mol, exposed during 10, 20 and 30 min, and incubated (25ºC, 7 days) to evaluate fungal inactivation. The O3 treated samples, when O3 exposed during the longest time (30 min/Day 7th) had the fungal growth totally inhibited (100%), while the others presented only reduced growth effect, i.e; 40 and 70 % for 10 and 20 min, respectively. Fusarium spores were not able to grow in any of the protein based sample studied (both, Control & Treated Group). On the other hand, Aspergillus and Penicilliun although grew on Control and some treated ones, their growth was inhibited by O3 depending on exposure time. That gas showed (under the conditions applied) to be fungi control effective for mackerel different forms of conservation.